Pharmacodynamics and Pharmacokinetics of Injectable Pimobendan and Its Metabolite, O-Desmethyl-Pimobendan, in Healthy Dogs - Pichayapaiboon, Poonavit; Tantisuwat, Lalida; Boonpala, Pakit; Saengklub, Nakkawee; Boonyarattanasoonthorn, Tussapon; Khemawoot, Phisit; Kijtawornrat, Anusak (Frontiers in Veterinary Science, 2021)
Objectives: This study was designed to thoroughly evaluate the effects of bolus pimobendan at a dose of 0.15 mg/kg on cardiac functions, hemodynamics, and electrocardiographic parameters together with the pharmacokinetic profile of pimobendan and its active metabolite, o-desmethyl-pimobendan (ODMP), in anesthetized dogs. Methods: Nine beagle dogs were anesthetized and instrumented to obtain left ventricular pressures, aortic pressures, cardiac outputs, right atrial pressures, pulmonary arterial pressures, pulmonary capillary wedge pressures, electrocardiograms. After baseline data were collected, dogs were given a single bolus of pimobendan, and the pharmacodynamic parameters were obtained at 10, 20, 30, 60, and 120 min. Meanwhile, the venous blood was collected at baseline and 2, 5, 10, 20, 30, 60, 120, 180, 360, and 1,440 min after administration for the determination of pharmacokinetic parameters. Results: Compared with baseline measurements, the left ventricular inotropic indices significantly increased in response to intravenous pimobendan, as inferred from the maximum rate of rise in the left ventricular pressure and the contractility index. Conversely, the left ventricular lusitropic parameters significantly decreased, as inferred from the maximum rate of fall in the left ventricular pressure and the left ventricular relaxation time constant. Significant increases were also noted in cardiac output and systolic blood pressure. Decreases were observed in the systemic vascular resistance, pulmonary vascular resistance, left ventricular end-diastolic pressure, pulmonary capillary wedge pressure, right atrial pressure, and pulmonary arterial pressure. The heart rate increased, but the PQ interval decreased. There was no arrhythmia during the observed period (2 h). The mean maximum plasma concentration (in µg/L) for ODMP was 30.0 ± 8.8. Pimobendan exerted large volume of distribution approximately 9 L/kg. Conclusions: Intravenous pimobendan at the recommended dose for dogs increased cardiac contraction and cardiac output, accelerated cardiac relaxation but decreased both vascular resistances. These mechanisms support the use of injectable pimobendan in acute heart failure.